Specialists and generalists - I. V. Anokhov (Управление)
The article considers labor specialization in terms of A.A. Bogdanov’s General Organizational Science (Tectology), whose methodology provides conclusions different from generally accepted A. Smith’s concept of labor division. The article’s goal is to investigate specialist’s characteristics and his difference from generalist.In terms of tectology, the difference is the cause of any process or phenomenon. Labor specialization is also based on difference – the difference between initial resources and collective consumption. The depth of labor specialization is determined by the number of people and the volume of their consumption. Reaching the global market’s limits has led to a reduction of differences in most markets and a decrease in production profitability, which in the long term can lead to the curtailment of material and energy flows. A qualitatively new difference may be the difference between the values and meanings of humanity, on the one hand, and the dehumanized technosphere, on the other. Subjects capable of linking these differences are generalists, capable of combining an understanding of the technosphere as a system, an awareness of long-term cause-and-effect relations, and the values and meanings of humanity.The scientific novelty of the findings obtained lies in studying labor specialization and the prospects of its transition to universalization and generalization.